Effects of DC-link filter on harmonic and interharmonic generation in three-phase adjustable speed drive systems - Soltani, H.; Davari, P.; Kumar, D.; Zare, Firuz; Blaabjerg, F. (2017)
© 2017 IEEE. Harmonic and interharmonic distortions are considered as the main power quality issues especially in the distribution networks. The double-stage Adjustable Speed Drives (ASDs) in which the front-end diode rectifier is connected to a rear-end inverter through an intermediate DC-link filter May inject significant amount of harmonics and interharmonics into the grid and consequently degrade the grid power quality. In this paper, the effect of the DC-link filter – as a key player – on the ASD input current harmonic and interharmonic distortions is investigated. In this respect, the ASD performance is evaluated harmonically based on three different DC-link configurations; the conventional filter (with AC- and/or DC-side chokes, and DC-link capacitor), the Small DC-Link Capacitor (SDLC), and the controlled DC link by using an Electronic Inductor (EI) technique. It shows how employing the small DC-link capacitor will push the harmonics into the higher frequency ranges and it will also give rise to more interharmonic distortions. Moreover, the EI configuration is introduced as an optimal DC-link intermediate circuit within the investigated frequency range of 0–2 kHz. The presented analysis and discussions have been validated by the simulation and experimental results.